The Holy See and the emergence of the modern Middle East : Benedict XV's diplomacy in Greater Syria (1914-1922) - Dreuzy, Agnes de (The Catholic University of America Press, 2016)
"This detailed analysis of Pope Benedict XV's wartime diplomacy in the Levant focuses on relations between the Holy See and the European powers with Middle Eastern interests (France, Britain, and Russia) as well as the Ottoman Empire, and sheds new light on the intricate relationships between churches of the Eastern Rite (Maronites, Melkites) and those of the Latin Rite. The author argues that far from being passive and ineffectual during World War I, Benedict XV vigorously pursued a nuanced foreign policy that shaped the history of the papacy through the 20th century"--